Endoplasmic reticulum homeostasis: a potential target for diabetic nephropathy - Yang, Ming; Liu, Chongbin; Jiang, Na; Liu, Yan; Luo, Shilu; Li, Chenrui; Zhao, Hao; Han, Yachun; Chen, Wei; Li, Li; Xiao, Li; Sun, Lin (Frontiers in Endocrinology, 2023)
The endoplasmic reticulum (ER) is the most vigorous organelle in intracellular metabolism and is involved in physiological processes such as protein and lipid synthesis and calcium ion transport. Recently, the abnormal function of the ER has also been reported to be involved in the progression of kidney disease, especially in diabetic nephropathy (DN). Here, we reviewed the function of the ER and summarized the regulation of homeostasis through the UPR and ER-phagy. Then, we also reviewed the role of abnormal ER homeostasis in residential renal cells in DN. Finally, some ER stress activators and inhibitors were also summarized, and the possibility of maintaining ER homeostasis as a potential therapeutic target for DN was discussed.